Multiple Experiments for the Causal Link between the Quantity and Quality of Children - Angrist, Joshua; Lavy, Victor; Schlosser, Analia (Journal of Labor Economics, 2010)
This article presents evidence on the child-quantity/child-quality trade-off using quasi-experimental variation due to twin births and preferences for a mixed sibling sex composition, as well as ethnic differences in the effects of these variables. Our sample includes groups with very high fertility. An innovation in our econometric approach is the juxtaposition of results from multiple instrumental variables strategies, capturing the effects of fertility over different ranges for different sorts of people. To increase precision, we develop an estimator that combines different instrument sets across partially overlapping parity-specific subsamples. Our results are remarkably consistent in showing no evidence of a quantity-quality trade-off.